Photovoltaic and wind energy systems monitoring and building energy management using ZigBee devices within a smart grid - Melício, Rui (2013)
The actual electric grid was developed to offer electricity to the clients from centralized generation, so with large-scale distributed renewable generation there is an urgent need for a more flexible, reliable and smarter grid. The wireless technologies are becoming an important asset in the smart grid, particularly the ZigBee devices. These smart devices are gaining increased acceptance, not only for home and building automation, but also for energy management, efficiency optimization and metering services, being able to operate for long periods of time without maintenance needs. In this context, this paper provides new comprehensive field tests using open source tools with ZigBee technologies for monitoring photovoltaic and wind energy systems, and also for building energy management. Our experimental results demonstrate the proficiency of ZigBee devices applied in distributed renewable generation and smart metering systems.